Analisis Pembentukan Selera Musik Dangdut di Kalangan Remaja: Studi Kasus Siswa SMA Negeri Kerjo - Andhata, Danar; Setiaji, Denis (Lembaga Yasin AlSys, 2025)
Although adolescents’ musical tastes have been widely examined, studies that specifically explain the mechanisms underlying the formation of dangdut musical preferences through Pierre Bourdieu’s framework of habitus, capital, and field in the context of secondary schools remain limited. This study aimed to explain how habitus, forms of capital, and the configuration of the social field contribute to shaping dangdut music preferences among students of SMA Negeri Kerjo. The research employed a qualitative and quantitative approach with a case study design, collecting data through participant observation, interviews with students who favor dangdut and key informants (dangdut singers, Art and Culture teachers, and event organizers), as well as document analysis of Google Forms survey results and digital traces on social media. Informants were selected using purposive and snowball sampling techniques, while data were analyzed thematically within Bourdieu’s theoretical perspective. The findings show that dangdut music preferences are formed through interactions across four spatial spheres: the private sphere (exposure and practice within the family/home), the communal sphere (activities with peers and communities), the formal/institutional sphere (legitimation through classroom playback and performances in official school events), and the digital sphere (the circulation of songs, trends, and content production on platforms such as TikTok and Instagram). Interactions among these spheres enable the reproduction of musical habitus, the conversion of various forms of capital (cultural, social, economic, and digital) into symbolic capital, and the acceleration of the diffusion and legitimation of dangdut within adolescents’ identity repertoires. These findings contribute to the development of the sociology of music by demonstrating that adolescents’ musical taste is not merely an individual choice, but a socially constructed preference structured within the educational field and popular culture.